2017
DOI: 10.5209/reve.54926
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativismo 2.0: presencia en Internet y desarrollo del comercio electrónico en las cooperativas oleícolas de Cataluña

Abstract: Resumen. El papel de las TIC en la gestión empresarial constituye actualmente un tema de creciente interés tanto para académicos como para profesionales. La Web 2.0 se ha revelado como una importante fuente de innovación que contribuye al desempeño organizacional y a la mejora de la competitividad de las empresas del sector agrario. A pesar de ello, se han encontrado evidencias que revelan las dificultades para la entrada de estas tecnologías en las empresas del sector agroindustrial y su aplicación para un ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
(25 reference statements)
0
6
0
7
Order By: Relevance
“…To analyze website quality, we used the eMICA technique [51], which is based on the work of Burgess and Cooper [52,53]. In recent years, the eMICA has been one of the most widely used models to analyze the adoption of ICTs and e-commerce across a range of sectors [54][55][56][57][58][59].…”
Section: Extended Model Of Internet Commerce Adoption (Emica)mentioning
confidence: 99%
See 3 more Smart Citations
“…To analyze website quality, we used the eMICA technique [51], which is based on the work of Burgess and Cooper [52,53]. In recent years, the eMICA has been one of the most widely used models to analyze the adoption of ICTs and e-commerce across a range of sectors [54][55][56][57][58][59].…”
Section: Extended Model Of Internet Commerce Adoption (Emica)mentioning
confidence: 99%
“…Each layer consists of items that take the value 1 (indicating presence) or 0 (indicating absence). To obtain the indicators for this procedure, we drew on a prior study [59] of the olive oil sector of a Spanish region (Table 1). Access to company's social network profiles F2.N3.…”
Section: Extended Model Of Internet Commerce Adoption (Emica)mentioning
confidence: 99%
See 2 more Smart Citations
“…In short, as Cristóbal et al [39], although these digital technologies have revealed themselves as an important source of innovation that contributes to the improvement of the competitiveness of the agri-cooperatives, in this sector, there is evidence revealing the difficulties for the implementation of these technologies and their application for effective electronic commerce, all in spite of the fact that these tools offer an important opportunity for the fulfillment of some of its main functions, such as promoting, coordinating, and developing common economic goals of its partners and strengthening and integrating their economic activity. In any case, it should be borne in mind that investing in digital technologies is not enough to be more competitive, but it is necessary to understand the technology, and how to make adequate use of it [18,40].…”
Section: New Challenges For the Agricultural Sector: The Smart Agri-cmentioning
confidence: 94%